PERANCANGAN SISTEM MONITORING ONLINE PADA PASIEN PENDERITA JANTUNG KORONER BERBASIS IDENTIFIKASI SINYAL ELEVASI ST - Ratna Adil (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
The coronary heart disease is one of desease leading to the sudden death. This is the reason why online  monitoring system is urgently needed to monitor the patients with coronary heart disease. This paper proposse the system with an algorithm which is developed from signal identification of ST elevation. The medical record in this system is measured by a new wireless ECG development and followed Zigbee standard. If the system detects the possibility of disturbance in cardiac function, then soon, an alarm signal is send to the server at the hospital, in order that an intensive first aid can be given immediately. Based on the testing results, the level of success of an online monitoring system is possible to reach 100% if the patient does not make any moving around. It is expected that the application of this system will reduce the sudden death for patients at hospital with coronary heart disease.